2022
DOI: 10.3390/molecules27238554
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Low-Molecular-Weight Organics by Water-Soluble Macrocyclic Arenes

Abstract: In this study, we fabricate a series of water-soluble anionic macrocyclic arenes, including pillar[5]arene (WP5), pillar[6]arene (WP6), leaning pillar[6]arene (WLT6), and biphenyl-extended pillar[6]arene (WBpP6), which show different separation capabilities toward low-molecular-weight organics, such as short chain haloalkanes, cyclic aliphatics, and aromatics, in water. The liquid–liquid distribution experiments are carried out at room temperature. The separation factor for low-molecular-weight organics is eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In comparison with inorganic composites, the significant downside of organic materials is the less thermal stability and weaker fatigue resistance. Thus, the future design of DTD-based optical storage systems must focus on the DTE materials equipped with intense structure rigidity, strong anti-interference performance, and large conjugated frameworks, which is expected to be achieved by introducing conjugated blocks such as macrocyclic hosts, long chains of polymers, and coordination frameworks, for meeting the requirements of rewritable and non-destructive recordings with large storage capacity, no signal crosstalk, and high signal-to-noise ratio [ 79 , 80 , 81 , 82 ].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…In comparison with inorganic composites, the significant downside of organic materials is the less thermal stability and weaker fatigue resistance. Thus, the future design of DTD-based optical storage systems must focus on the DTE materials equipped with intense structure rigidity, strong anti-interference performance, and large conjugated frameworks, which is expected to be achieved by introducing conjugated blocks such as macrocyclic hosts, long chains of polymers, and coordination frameworks, for meeting the requirements of rewritable and non-destructive recordings with large storage capacity, no signal crosstalk, and high signal-to-noise ratio [ 79 , 80 , 81 , 82 ].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Porous materials-based adsorptive separation technology has been recognized as an alternative strategy for the separation of cyclic aliphatic and aromatic hydrocarbons, owing to its high efficiency and low energy consumption. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In recent years, various adsorbents such as metal-organic frameworks (MOFs), 24 porous organic molecular frameworks (POMFs), 25 organic macrocycles, [26][27][28] and molecular cages 29 have been reported for the separation of MCH and Tol. Typically, these examples showed that MCH and Tol could be selectively adsorbed into the extrinsic void of assembled materials or the intrinsic cavity of macrocycles, depending on the differences in their molecular sizes, conformational structures, and electrical charge distributions.…”
mentioning
confidence: 99%
“…[32][33][34] Water soluble macrocyclic arenes have the ability to recognize and assemble in water, which is of practical signicance for understanding and mimicking biological processes. [35][36][37][38] By introducing the water soluble groups into suitable positions on the macrocyclic arenes, water-soluble macrocyclics can be easily obtained. Water soluble carboxylatopillar[n]arenes [39][40][41][42] and psulfonatocalix[n]arenes [43][44][45] have gained maximum popularity for their easy preparation, p-electron rich hydrophobic cavity, ideal candidates for host-guest binding with cationic guests and application in fabricating responsive supramolecular systems and as nanovalves for trapping and releasing cargo molecules.…”
mentioning
confidence: 99%